Fanatisme dan Ekspresi Simbolik Suporter Sepak Bola Panser Biru dan SNEX Semarang: Kajian Etnografis - Muhammad Fathan Mubina; Amirudin Amirudin; Af'idatul Lathifah (Endogami: Jurnal Ilmiah Kajian Antropologi, 2020)
The fanaticism of football supporters among PSIS Semarang supporters, namely Panser Biru and Snex, is seen as a form of solidarity that exists between consentient individuals who are united based on the similarity of their love for the PSIS Semarang team. This paper aims to describe the forms of fanaticism PSIS supporters, forms and patterns of symbolic expression of PSIS supporters and the relationship between fanaticism and symbolic expressions created by PSIS Semarang supporters. This study uses ethnographic methods with data collection techniques such as participatory observation, in-depth interviews, and literature study. This study uses the consumer culture theory by Celia Lury. The approach used to study this research is symbolic interactionism by Agus Maladi Irianto. Based on research findings, the fanaticism form of PSIS supporters is the use of attributes by Panser Biru and Snex supporters, unlimited loyalty in supporting PSIS, love, and totality in supporting PSIS, introducing and educating children about PSIS from an early age. The forms and patterns of the symbolic expression of the Panser Biru and Snex supporters include the choreography, mural, banners, criticism, and also the fan chants of the Panser Biru and Snex for PSIS Semarang. Fanaticism appears to symbolic expressions and all forms of symbolic expression are related to their fanaticism (Panser Biru and Snex). The meaning of the supporters of what they have done is what expresses the fanaticism of the individual PSIS supporters. The form of relationship between fanaticism and symbolic expression is the choreography and chants displayed while in the stadium means showing their fanaticism towards PSIS in the form of love and totality so that during support Through choreography and chants carried out with sincerity and maximums to positively impact the result of the match because of the influence of supporters’ support that keeps the spirit of the player when competing very large.